The Mediating Role of Resilience and Diabetes Distress in Relationship between Depression and Treatment adherence in type 2 Diabetic among Iranian patients - masoumeh Rahimi; Mahsa Jalali; Rababeh Nouri; Mojgan Rahimi (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: The coexistence of mental health problems in diabetic patients can lead to poor disease management. This study aimed at investigating the mediating role of resilience and diabetes distress in the relationship between depression and treatment adherence in type 2 diabetes among Iranian patients. Methods: It is a type of analytical study conducted from 2019 to 2020. The statistical population of this study consisted of all-diabetic patients in Tehran. The subjects (200) were selected after purposeful clinical evaluation and qualification of research. In this study, Beck Depression Inventory (BDI), the Persian Version of the Morisky Medication Adherence Scale-8, Diabetes Distress Scale (DDS), Conner & Davison Resilience Scale (CDRS) were used to collect the data. Pearson correlation test by SPSS version 24 and Confirmatory Factor Analysis in AMOS software version 22 were used for analysis (P<0.05). Results: In the present study, most participants (about 36.5%) were in the age group of 56-65 and 58.5% of them were female. According to the results, the variables of depression and diabetes distress has a negative and significant correlation with adherence to treatment (r= -.408, p<0.05). The resiliency has a positive and significant correlation with adherence to treatment (r= 0.414, p<0.05). Conclusion: The findings showed a link between depression, diabetes distress, resilience, and treatment adherence. Resilience and anxiety from diabetes play a mediating role between depression and adherence to care.  Paying attention to patient resilience may lead to improved depression and diabetes distress in patients with diabetes, to increase the patient's involvement in treatment adherence.